2003
DOI: 10.1111/j.0014-3820.2003.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hybridization Between African and European Honeybees, Apis Mellifera, on Asymmetries in Wing Size and Shape

Abstract: Abstract.We examined the possible role of hybridization in the invasion process of the African honeybee by testing two hypotheses regarding fluctuating asymmetry (FA), a measure of developmental stability, in wing characteristics: (1) FA should be higher in hybrid versus parental genotypes of African and European races; (2) FA should be lower in African bees compared to hybrid and European workers. Parental and reciprocal hybrid worker genotypes were cross fostered in common-hive rearing environments. We did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 72 publications
4
23
1
2
Order By: Relevance
“…Directional asymmetry is not a rare effect in Diptera PĂ©labon and Hansen, 2008;Soto et al, 2010), as well in other invertebrate (Graham et al, 1998;Schneider et al, 2003) and vertebrate groups (Kark, 2001;Marchand et al, 2003;Loehr et al, 2013). In Diptera, suggested that the genetic basis of DA has been conserved over evolutionary time due to the existence of a left-right axis determining the position of imaginal disks (developmental precursors of wings) on each side of the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Directional asymmetry is not a rare effect in Diptera PĂ©labon and Hansen, 2008;Soto et al, 2010), as well in other invertebrate (Graham et al, 1998;Schneider et al, 2003) and vertebrate groups (Kark, 2001;Marchand et al, 2003;Loehr et al, 2013). In Diptera, suggested that the genetic basis of DA has been conserved over evolutionary time due to the existence of a left-right axis determining the position of imaginal disks (developmental precursors of wings) on each side of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Given that NA is composed of both FA and DA, NA can be partitioned into those two types of asymmetry (Graham et al, 1998;Marchand et al, 2003). The population estimate of DA was obtained by calculating the Procrustes distance between the average of the left and right configurations of each population (Schneider et al, 2003), whereas the difference between NA and DA was considered as a population-level estimate of FA (Marchand et al, 2003). Therefore, the values of individual fluctuating asymmetry (FAi) were obtained by calculating the difference between NAi and DA of each specimen.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Depending on the type, magnitude, and sign of the epistatic effects, FA levels in these characters would be expected to respond differently (increase, decrease, or show no change) to various stressors such as inbreeding or selection (Leamy et al 2005). Clearly the choice of characters in FA analyses is critical (Indrasamy et al 2000, Woods et al 1999) and may account for many ambiguous results in FA studies, including those cases in which no differences in FA levels have been detected between various parental races or subspecies and their hybrid offspring (Alibert & Auffray 2003, Schneider et al 2003.…”
Section: Implications Of the Hypothesismentioning
confidence: 99%
“…Wing shape variation of insects at different taxonomic levels have been studied using GM (De La Riva et al 2001;Pretorius and Scholtz 2001;Monteiro et al 2002;Houle et al 2003;Schachter-Broide et al 2004;Pretorius 2005;Aytekin et al 2007;Sadeghi et al 2009). In addition, wing shape variation based on GM has been used to discriminate and identify honeybee subspecies (Francoy et al 2008;Tofilski 2008), the heritability of wing shape (Monteiro et al 2002) and the influence of hybridization on fluctuating asymetry (Schneider et al 2003). Traditional morphometry including both wing and body characters has provided substantial insight into and good discrimination among honeybee subspecies and populations (Diniz-Filho et al 2000;Ruttner et al 2000;Kandemir et al 2000), although standard morphometry of wing characters alone provides less resolution than geometric morphometry (Tofilski 2008).…”
Section: Introductionmentioning
confidence: 99%